Nutritional composition and angiotensin-converting enzyme inhibitory activity of blue lupin (Lupinus angustifolius L.) - Chin, Ying Yee (2017)
Angiotensin-converting enzyme (ACE) plays a dominant role in blood pressure regulating system. Synthetic ACE inhibitor is designed as an antihypertensive drug to restrict ACE activity. However, the usage of synthetic drug may cause several adverse effects. Hence, a natural food protein with ACE inhibitory activity may be promising as a safer alternative to the synthetic drug. Blue lupin (Lupinus angustifolius) is one of the legumes that rich in protein. It has the potential to be a good source of ACE inhibitory peptides. However, blue lupin is usually served as an animal feed and consumption by human is rare. Therefore, this study was carried out to investigate the nutritional, protein and amino acid composition of blue lupin flour, and to evaluate the ACE inhibitory activity of its protein hydrolysates. The results revealed that the lupin flour was abundant in protein (43.3 g/100 g) and dietary fibre (33.5 g/100 g). According to the Osborne classification, plant storage protein was characterised into four categories based on their solubility in different solvents. Results from sequential Osborne extraction procedure showed that lupin protein comprised of 46% salt-soluble globulin, 27% water-soluble albumin, 18% alkaline-soluble glutelin and 7% alcohol-soluble prolamin fractions. Furthermore, lupin protein was rich in lysine but limiting in methionine. In this study, Alcalase and Flavourzyme were used to hydrolyse the lupin protein isolate for different hydrolysis times (4, 10 and 16 h). Gel electrophoresis analysis demonstrated that protein hydrolysis catalysed by Alcalase was more effective compared with Flavourzyme as evidenced by the lower molecular weight peptides presented in the hydrolysates prepared using Alcalase. The ACE inhibitory activity of hydrolysates was determined using an in vitro method. Hydrolysates prepared using Alcalase exhibited higher ACE inhibitory activities compared with those prepared using Flavourzyme, showing IC50 values ranging from 0.10 to 0.21 mg/mL. However, there was no significant difference in IC50 values between the hydrolysates prepared using Alcalase for 4, 10 and 16 h of hydrolysis times. The results suggested that globulin was the major contributing protein fraction on ACE inhibitory effect in lupin protein. In addition, the information obtained in this study is important to reveal the nutritional values and health benefits of blue lupin protein and to recognise the lupin protein hydrolysates as nutraceuticals or functional foods. The lupin protein hydrolysates with potent ACE inhibitory activities can be incorporated into the daily diet to prevent hypertension. They can also be consumed by hypertensive patients to reduce the dosage of antihypertensive drugs needed, thereby lowering the risk of side effects.